2012
DOI: 10.1590/s0037-86822012000300019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of new cases of leprosy in the State of Espírito Santo, Brazil, between 2004 and 2009

Abstract: INTRODUCTION: Leprosy in Brazil is a public health issue, and there are many regions in the State of Espírito Santo with high endemic incidence levels of leprosy, characterizing this state as a priority for leprosy programs. The aim of this study was to determine the spatial distribution of coefficients of new cases of leprosy in the State of Espírito Santo, Brazil. METHODS: We conducted a descriptive and ecologic study based on the spatial distribution of leprosy in the State of Espírito Santo between 2004 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
2
4
0
3
Order By: Relevance
“…Table 1, Table 2 and Table 3 show the articles' summaries according to the scale used: two evaluated regions/ mesoregions 14,15 ; 13 used the scale of municipalities 10,[16][17][18][19][20][21][22][23][24][25][26][27] ; 4 evaluated districts [28][29][30][31] ; 6 studied neighborhoods [32][33][34][35][36][37] ; 7 analyzed the census tracts [38][39][40][41][42][43][44] ; and 3 investigated households [45][46][47] . Within each scale, the articles were organized by location: Brazil, Northern, Northeast, Midwest, and Southeast regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1, Table 2 and Table 3 show the articles' summaries according to the scale used: two evaluated regions/ mesoregions 14,15 ; 13 used the scale of municipalities 10,[16][17][18][19][20][21][22][23][24][25][26][27] ; 4 evaluated districts [28][29][30][31] ; 6 studied neighborhoods [32][33][34][35][36][37] ; 7 analyzed the census tracts [38][39][40][41][42][43][44] ; and 3 investigated households [45][46][47] . Within each scale, the articles were organized by location: Brazil, Northern, Northeast, Midwest, and Southeast regions.…”
Section: Resultsmentioning
confidence: 99%
“…Within each scale, the articles were organized by location: Brazil, Northern, Northeast, Midwest, and Southeast regions. In all, 4 approached Brazil 10,16-18 , 7 studied the Northern region or the states of the Amazon region 14,19,20,[38][39][40]45 , 11 focused on the Northeast region [21][22][23]28,[32][33][34][35][36]40,41 , 4 the Midwest region 15,29,37,46 , and 12 the Southeast region [24][25][26][27]30,31,36,37,[42][43][44]47 .…”
Section: Resultsmentioning
confidence: 99%
“…A spatially empirical Bayes smoothed case detection rate has been used in leprosy studies to smooth the random variations in small areas with few people (where small variations in the number of cases results in dramatic changes in disease rates) and to enhance the visualization of spatial patterns [17], [50][52]. Smoothing is also a way to estimate uncertain values for areas with no registered cases, areas where disease is not necessarily absent but may not have been detected due to operational limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that the new cases detected during the course of 10 years were heterogeneously distributed throughout the city area, in accordance with the epidemiologic indicators, and corroborating with other studies that employed spatial geographic analysis in settings highly endemic for leprosy (28,29). Different detection rates were observed within different neighbourhood sectors, varying between low and hyperendemic, following the official parameters for the annual detection rate.…”
Section: Discussionsupporting
confidence: 89%